Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Daguerreotype photo of Florence Wrinkle Ottinger by herself and with her husband Jim Ottinger; Florence was a sister of Maryanne Watkins